AGN Broad Line Region Variability in the Context of Eigenvector 1: Case of NGC 5548 - Bon, Nataša; Bon, Edi; Marziani, Paola (Frontiers in Astronomy and Space Sciences, 2018)
Many active galactic nuclei (AGN) show strong variability of the optical continuum. Since the line flux, profile shapes and intensity ratios are changing, we analyze the variability patterns and possible periodicity of Type 1 AGN NGC 5548, using the Eigenvector 1 (EV1) diagram in different variability states, taking advantage of very long term monitoring campaign data. The preliminary results suggest that NGC 5548—a highly variable object that over several decades has shown large amplitude continuum fluctuations and flaring behavior—remains Pop B. This means that the range in Eddington ratio, even when the source is in a bright state, remains consistent with the value of the low accreting Pop B. We inspected EV 1 parameters of a single object though long term monitoring, assuming an inclination and black hole mass to be constant during the observational time. Our results imply that the main driver for the variations along the EV 1 diagram could be dimensionless accretion rate. If so, then it appears that the source never crossed the boundary for structural changes, indicatively placed at L/LEdd ~ 0.2.